Evaluation Of Image Quality And Radiation Dose On Gold Nanoparticles And Other Clinical Contrast Agents In Abdominal Computed Tomography Phantom - Zukhi, Nur Jihan Mohd (2018)
Some medical conditions need multiple contrast agents’ administration when multiple target organs are needed for diagnostic imaging. Currently, there is no abdominal phantom that can analyse the image quality of multiple contrast agents and radiation dose simultaneously. Thus, the gold nanoparticles and other clinical contrast agents were used in this study using a fabricated abdominal phantom. The aim of this study was to evaluate the image quality and radiation dose using several contrast agents (gold nanoparticles, barium, iodine, gadolinium, and milk) in abdominal computed tomography (CT) phantom. Abdomen phantom of 32 cm diameter was fabricated from polymethyl methacrylate with five sets of optically stimulated luminescence dosimeter slots and the cylindrical contrast agent tubes with 6 cm diameter that attached together.